Environmental degradation amplifies species' responses to temperature variation in a trophic interaction. Issue 11 (11th August 2019) - Mugabo, Marianne; Gilljam, David; Petteway, Laura; Yuan, Chenggui; Fowler, Mike S.; Sait, Steven M.
Abstract: Land‐use and climate change are two of the primary drivers of the current biodiversity crisis. However, we lack understanding of how single‐species and multispecies associations are affected by interactions between multiple environmental stressors. We address this gap by examining how environmental degradation interacts with daily stochastic temperature variation to affect individual life history and population dynamics in a host–parasitoid trophic interaction, using the Indian meal moth, Plodia interpunctella, and its parasitoid wasp Venturia canescens . We carried out a single‐generation individual life‐history experiment and a multigeneration microcosm experiment during which individuals and microcosms were maintained at a mean temperature of 26°C that was either kept constant or varied stochastically, at four levels of host resource degradation, in the presence or absence of parasitoids. At the individual level, resource degradation increased juvenile development time and decreased adult body size in both species. Parasitoids were more sensitive to temperature variation than their hosts, with a shorter juvenile stage duration than in constant temperatures and a longer adult life span in moderately degraded environments. Resource degradation also altered the host's response to temperature variation, leading to a longer juvenile development time at high resource degradation. At the population level, moderate resource degradation amplified the effects of temperature variation on host and parasitoid populations compared with no or high resource degradation and parasitoid overall abundance was lower in fluctuating temperatures. Top‐down regulation by the parasitoid and bottom‐up regulation driven by resource degradation contributed to more than 50% of host and parasitoid population responses to temperature variation. Our results demonstrate that environmental degradation can strongly affect how species in a trophic interaction respond to short‐term temperature fluctuations through direct and indirect trait‐mediated effects. These effects are driven by species differences in sensitivity to environmental conditions and modulate top‐down (parasitism) and bottom‐up (resource) regulation. This study highlights the need to account for differences in the sensitivity of species' traits to environmental stressors to understand how interacting species will respond to simultaneous anthropogenic changes. Abstract : Species are often exposed simultaneously to multiple anthropogenic stressors, but their impacts have mainly been studied independently and in single species. The authors demonstrate that environmental degradation amplifies species' responses to fluctuating temperatures by directly altering individual life‐history traits and by indirectly affecting top‐down and bottom‐up regulations in a host‐parasitoid trophic interaction.